Value creation and the circular economy: A tale of three externalities. (2nd August 2022) - Figge, Frank; Thorpe, Andrea Stevenson; Manzhynski, Siarhei
Abstract: By using resources more efficiently, resource users help to overcome the inherent resource scarcity on "spaceship earth." One strategy in this context is to close resource loops and to use resources circularly. With fewer resources wasted, a more circular use of resources should also increase the efficiency of resource use and create more value. However, when resource users aim for a greater degree of efficiency, inadvertently they might contribute to resources being used less rather than more circularly and, consequently, less instead of more efficiently. We show how to assess the value that is created by the efficient use of resources for the case of linear and circular resource use. This allows us to identify three distinct types of positive externalities related to the circular use of resources: (1) systemic static externalities; (2) idiosyncratic dynamic externalities; and (3) systemic dynamic externalities. We describe how the value created by these externalities can be assessed and argue that they need to be considered when evaluating environmental resource use.